Burial or Not: The Case of Pamayugan 2 stone boat-shaped markers - Dizon, Eusebio Z.; Valientes, Edwin A.; Ragragio, Andrea Malaya M.; Mijares, Armand Salvador B. (Hukay; Vol 12, 2014)
In 2006, a team from the National Museum of the Philippines and the UP Archaeological Studies Program excavated two stone boat-shaped markers at Pamayugan 2, Itbayat lsland. The aim of the excavation was to recover human remains and datable materials. No human remains were recovered, which puzzled the team. The Hypothesis that the human remains did not survive due to the high acidity of the soil has been tested, and seems plausible.